PRKCSH serves as a potential immunological and prognostic biomarker in pan-cancer - Qiankun Wang; Xiong Wang; Jiaoyuan Li; Tongxin Yin; Yi Wang; Liming Cheng (Scientific Reports, 2024)
Abstract Protein kinase C substrate 80K-H (PRKCSH) plays a crucial role in the protein N-terminal glycosylation process, with emerging evidence implicating its involvement in tumorigenesis. To comprehensively assess PRKCSH’s significance across cancers, we conducted a pan-cancer analysis using data from The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), and Cancer Cell Line Encyclopedia (CCLE). We assessed aberrant PRKCSH mRNA and protein expression, examined its prognostic implications, and identified correlations with clinical features, tumor mutational burden (TMB), microsatellite instability (MSI), and tumor immunity across cancer types. We explored PRKCSH gene alterations, DNA methylation, and their impact on patient prognosis. Gene Set Enrichment Analysis (GSEA) and single-cell analysis revealed potential biological roles. Additionally, we investigated drug susceptibility and conducted Connectivity Map (Cmap) analysis. Key findings revealed that PRKCSH exhibited overexpression in most tumors, with a significant association with poor overall survival (OS) in six cancer types. Notably, PRKCSH expression demonstrated variations across disease stages, primarily increasing in advanced stages among eleven tumor types. Moreover, PRKCSH exhibited significant correlations with TMB in five cancer categories, MSI in eight, and displayed associations with immune cell populations in pan-cancer analysis. Genetic variations in PRKCSH were identified across 26 tumor types, suggesting favorable disease-free survival. Furthermore, PRKCSH methylation displayed a significant negative correlation with its expression in 27 tumor types, with a marked decrease compared to normal tissues in ten tumors. Cmap predicted 24 potential therapeutic small molecules in over four cancer types. This study highlights that PRKCSH, as a potential oncogene, may be a promising prognostic marker and therapeutic target of immunotherapy for a range of malignancies.